Conjoined Stent Technique for Radiation Induced Long Segment Carotid Stenosis and Pseudoaneurysm - Atulabh Vajpayee (Neurointervention, 2014)
Radiation induced carotid stenosis (RICS) is known but challenging complication of head and neck irradiation. Endovascular revascularization is preferred treatment modality than surgical revascularization. Sometimes endovascular treatment may be difficult in view of long segment of stenosis and associated pseudoaneurysm. We report a unique technique of carotid stenting named as "conjoined stent technique" in a challenging case of RICS with long segment of stenosis and pseudoaneurysm. In this technique we overlapped distal end of one stent with proximal end of second stent to occlude pseudoaneurysm. "Conjoined stent technique" may be viable option in case of long segment of RICS with associated pseudoaneurysm and alternative to flow diverters in extracranial carotid pseudoaneurysm.